MODIFIKASI APLIKASI BIOMASSA (BIOCHAR, PUPUK KANDANG DAN JERAMI JAGUNG) PADA PERTANAMAN UBI KAYU DI TANAH LEMPUNG BERPASIR (SANDY LOAM) LAHAN KERING LOMBOK UTARA - Sukartono Sukartono; Suwardji Suwardji; Mulyati Mulyati; Baharuddin Baharuddin; Tejo Wulan (BUANA SAINS, 2014)
Improved management of dryland agriculture could be one strategy to increase cassava production in order to meet national demand particularly for food and bioetanol industry. A field experiment was carried out to evaluate the influence of biomass modification addition (biochar, cattle manure, and corn-straw) on the growth and yield of cassava grown on sandy soils of northern Lombok. The treatments tested were: without addition of organic biomas as control (M0); the straw was put in the lowest part of rhyzoshere, biochar in the middle and subsequently followed by manure mixed with soil on top (M1); biochar, cattle manure, straw were mixed thoroughly within rhyzosphre (M2); biochar and cattle manure were only mixed with soil (M3); the manure was put down in the bottom part of rhyzoshere, straw in the middle and subsequently followed by biochar mixed with soil on top (M4). Results of the research showed that modification of biomass addition (biochar, manure and corn-straw) within soil increased significantly the growth and yiled as a results of better nutrient retention compared to soil without organic addition. The yield was increased by 32 and 33% at M1 and M4 respectivelly and reached closed to 40% at treatments of both M2 and M3 (27 ton ha-1)